Heat and mass transfer processes in drug aerosol flows in a human proximal respiratory tract; Journal of Aerosol Science; Vol. 193 - Antonov D. V. Dmitry Vladimirovich; Nagatkina O. V. Olga Vladimirovna; Aynetdinova E. S. Elizaveta Sergeevna; Sazhin S. S. Sergey Stepanovich (2026, 2026)
Title screen